Improvement of blood donor knowledge in community at Sumbertlaseh, Bojonegoro - Nina Difla Muflikhah; Fatia Rizki Nuraini; Eva Riantika Ratna Palupi; Titik Nuryanti; Retno Puji Astuti (Universitas Muhammadiyah Magelang, 2023)
Blood services is one of the health support systems which play important role for fulfilling blood stock, blood production, and distribution. Fulfilment of blood stock become the main focus of blood support unit in Indonesia. During the Covid-19 pandemic, Indonesia Government applied community activities restrictions enforcement which social distancing became the major reason for decreasing donor quantity in Bojonegoro while blood supply was needed from other units. In case of increasing blood donor, socialization programme held at Sumbertlaseh Village. This programme accommodated by Student of diploma programme of blood bank technology, undergraduate programme of ners, dan Blood Donor Unit Bojonegoro. The programme share information about the important and advantage of blood donor using various media, such as brochure, leaflet, and presentation. The results of the activity show that 78.26% of the community has good knowledge about blood donor.